2001
DOI: 10.1006/dbio.2001.0255
|View full text |Cite
|
Sign up to set email alerts
|

Tantalus, a Novel ASX-Interacting Protein with Tissue-Specific Functions

Abstract: The Drosophila trithorax- and Polycomb-group (trxG and PcG) proteins maintain activated and repressed transcriptional states at specific target gene loci. The Additional sex combs (Asx) gene is of particular interest as it appears to function in both protein complexes and yet its effects on target genes are more restricted. A novel protein, Tantalus (TAN), was identified in a yeast two-hybrid screen for ASX-interacting proteins that might confer tissue-specific ASX functions. TAN contains consensus nuclear loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…This suggests that if the interaction between the ASXL proteins and Calypso/BAP1-like proteins is indeed mediated by the ASXH domain, then it might be an animal-specific feature of the domain. Another potential animal-specific binding partner of the ASXL proteins is prototyped by the Drosophila Tantalus protein, 34 whose orthologs we identified for the first time in other metazoans (Sup. Material).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that if the interaction between the ASXL proteins and Calypso/BAP1-like proteins is indeed mediated by the ASXH domain, then it might be an animal-specific feature of the domain. Another potential animal-specific binding partner of the ASXL proteins is prototyped by the Drosophila Tantalus protein, 34 whose orthologs we identified for the first time in other metazoans (Sup. Material).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, recent studies have shown that ASXL1, one of the three human orthologs of the Drosophila Additional sex combs (Asx) gene, [30][31][32][33] an enhancer of both the polycomb and trithorax group genes, 34 is a major target of mutations leading to myeloproliferative and myelodysplastic conditions, including acute myeloid leukemia, polycythemia vera, essential thrombocythemia and primitive myelofibrosis. 24,[35][36][37][38][39][40] ASXL1 mutations along with those in another polycomb group gene EZH2 are also indicative of poor overall survival in patients with myelodysplastic syndromes, independent of other known risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…All tan lines and constructs used here have been described previously (Dietrich et al 2001), and Gal4 driver lines used are described in Flybase (http://flystocks.bio.indiana.edu/ gal4.htm). The loss-of-function allele N 8 and the hypomorphic allele N 55e11 (described in Flybase) were crossed to either tan 2 homozygotes or P[tan];tan 2 homozygotes and the number of flies with four or fewer interocellar bristles were counted.…”
Section: Ectopic Expression and Genetic Analysismentioning
confidence: 99%
“…Although tan is expressed throughout embryogenesis and larval development, higher levels of expression are observed in some tissues (e.g. the morphogenetic furrow of the eye disc; Dietrich et al 2001). Flies homozygous for tan null mutations exhibit a variety of sensory organ defects including roughened eyes, bristle loss and duplication and minor defects in distal wing vein formation, but are otherwise viable and fertile.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation